The Development of Student Worksheets Based on Project Based Learning (PjBL) on The Topic of Biodiversity for Class X - Lingga, Trisnawaty Meriahna Br; Manurung, Binari (PROGRAM STUDI PENDIDIKAN BIOLOGI, 2025)
This research focuses on the development of Learner Worksheets (LKPD) based on interviews with biology teachers and observations of student needs. It was found that the use of LKPD is still rare, some have never used it, and the existing LKPD is not project-based. Therefore, LKPD is needed that can increase student creativity through project activities. The purpose of this study was to develop the LKPD, assess its feasibility (by material experts, learning experts, and design experts), and evaluate teacher and student responses, as well as its effectiveness on learning outcomes and student creativity. The development model used is the 4D model (Define, Design, Develop, Disseminate). LKPD is designed according to the needs of students and prepared based on LKPD preparation guidelines. The feasibility of LKPD was tested by material experts (87.14%), learning experts (97.33%), and design experts (77.33%) with very feasible and feasible categories. Teacher (97.33%) and student (92.96%) responses were also very positive. The LKPD was then tested on the experimental class X-A. Effectiveness was tested through pretest and posttest results which showed significant differences between experimental and control classes.